Pengaruh Latihan dan Pemanfaatan Peralatan Portable Monoplace Chamber Terhadap Keselamatan Penyelam Dislambair Koarmada II - Sugiarto Sugiarto; Budi Sugiarto; Panji Agung Nugroho (CV RIFAINSTITUT, 2025)
The Underwater Rescue Service (Dislambair) Koarmada II has the main task in underwater diving and rescue, where diver safety must be prioritized. This study aims to analyze the effectxof training in the operation and utilization of Portable Hyperbaric Chamber (PHC) on diver safety. The methodsused is a quantitative approach with a comparative causal design and quasi-experiment. Data were collected by distributing questionnaires to 35 active divers who have diving certificates. The results of the analysis show that both training (X1) and the utilization of PHC equipment (X2) have a significantspositive effect on diver safety (Y). Simple linear regression tests reveal that an increase in PHC operation training contributes with a coefficient of 0.619, while PHC utilization contributes 0.528. In addition, multiple regression analysis shows that the combination of both variables simultaneously contributes 73.4% to diver safety. This study emphasizes the importance of training and readiness in the utilization of PHC to improve safety, and recommends the formulation of a more systematic training policy for Dislambair Koarmada II divers to reduce the risk of decompression and increase the effectiveness of underwater operations